PENINGKATAN KEMAMPUAN REPRESENTASI MATEMATIS SISWA KELAS IX-G SMP NEGERI 2 BANDUNG PADA MATERI PERSAMAAN KUADRAT DENGAN DISCOVERY LEARNING MODEL - Siti Tuti Alawiyah; Jarnawi Afgani Dahlan (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2019)
Representative ability is the ability to express mathematical ideas that are used to show the results of his work in certain ways as a result of the interpretation of his mind. Based on the results of observations obtained data that the class on IX-G SMP 2 Bandung experienced a difficulty in presenting mathematical ideas. Difficulties experienced by students of class IX-G are a problem that must be addressed immediately because of how students can express mathematical ideas if students cannot develop representations properly. After the initial test, it turns out that the representation ability of students in class IX-G is in the low category. Based on the background of the problem found, the researcher carried out classroom action research to overcome the problems experienced by class IX-G. The objectives of this study are: (1) Knowing the increase in students' mathematical representation abilities with discovery learning models in class IX-G of SMP Negeri 2 Bandung. (2) Describing the response of students of class IX-G SMP Negeri 2 Bandung to the implementation of learning using discovery learning models. (3) Analyzing the effectiveness of the implementation of mathematics learning by using discovery learning models in improving the ability of mathematical representation. This classroom action research was conducted in 2 cycles. The subjects in this study were class IX-G, which amounted to 32 students consisting of 18 men and 14 women. Data collection was done using formative tests of mathematical representation abilities, student response questionnaires, and observation sheets of teacher and student activities. The results of this study as a whole have been successful because they have been able to improve students' representation abilities significantly and student learning outcomes are completed in a classical manner. This can be seen by the increase in the value of classical absorption ability of students' mathematical representation abilities from cycle I to cycle II. The absorption ability of students' mathematical representation in the first cycle was 31.25%, in the second cycle it increased to 87.50%. In addition, students' responses to learning are in good criteria. The effectiveness of implementing mathematics learning by using discovery learning models in improving the ability of mathematical representation is good.